2019
DOI: 10.1186/s12888-019-2209-1
|View full text |Cite
|
Sign up to set email alerts
|

What roles do male partners play in the mothering experiences of women living with mental illness? A qualitative secondary analysis

Abstract: Background Mothers who live with mental illness face diverse challenges. Research suggests that partner support or otherwise is likely to have a crucial influence on mothers’ abilities to manage these challenges, yet little is known about how this plays out. In this study, we aimed to explore the roles played by male partners in the mothering experiences of women living with mental illness. Methods We conducted a qualitative secondary analysis using interview data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, what this study finds is that it can be challenging when the role of caregiving or parenting from the other partner without mental illness is considered within the context of the families' separate living arrangements. Indeed, as with the previous studies (Awram et al, 2017;Beard et al, 2019), there are good days where the other partner without mental illness support to pay for the parent's medications, cover hospital bills, attends PTA, among others. The risk here is in overstating the supportive role by the partner without mental illness especially when the families are separated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, what this study finds is that it can be challenging when the role of caregiving or parenting from the other partner without mental illness is considered within the context of the families' separate living arrangements. Indeed, as with the previous studies (Awram et al, 2017;Beard et al, 2019), there are good days where the other partner without mental illness support to pay for the parent's medications, cover hospital bills, attends PTA, among others. The risk here is in overstating the supportive role by the partner without mental illness especially when the families are separated.…”
Section: Discussionmentioning
confidence: 67%
“…Another relationship or interactions in the micro‐system is the one the other partner has with the family. Studies have found that the partner without mental illness can play supportive roles to ensure that parenting is not compromised due to parental mental illness (Awram et al, 2017; Beard et al, 2019). Essentially, when the partner without mental illness is able to provide practical support, like respite services, it enables the other partner to balance their parenting and mental health recovery (Awram et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Women with schizophrenia are at considerable risk for interpersonal violence, a risk that increases during pregnancy. A recent population-based cohort study in Canada compared rates of interpersonal violence in women with and without schizophrenia who attended an emergency department (ED) while pregnant or within one year postpartum [64]. Measures taken were sociodemographic characteristics, history of substance use disorders, and interpersonal violence.…”
Section: Victimization During Pregnancy and Postpartummentioning
confidence: 99%
“…The literature shows that the stigma attached to mental illness can make it challenging for children to disclose parental mental illness to their peers or others outside the family (Grove et al, 2015; Källquist & Salzmann-Erikson, 2019). Because of the fear of isolation, stigma and judgments, parents are unwilling to disclose information about their mental illness to mental health professionals and others around them (Beard et al, 2019). The limitations to physical contacts might even make it more difficult for some families to talk with others about their mental illness.…”
Section: Adding Salt To Wounds?mentioning
confidence: 99%